2018
DOI: 10.2214/ajr.17.18680
|View full text |Cite
|
Sign up to set email alerts
|

MRI-Ultrasound Fusion Targeted Biopsy of Prostate Imaging Reporting and Data System Version 2 Category 5 Lesions Found False-Positive at Multiparametric Prostate MRI

Abstract: PI-RADS 5 lesions identified during routine clinical interpretation are associated with a high risk of clinically significant prostate cancer. A benign pathologic result was significantly correlated with lower prostate-specific antigen density and apex or base location and most commonly attributed to a benign prostatic hyperplasia nodule. Integration of these clinical features may improve the interpretation of high-risk lesions identified with mpMRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
3
19
0
Order By: Relevance
“…Other studies describe rates for malignancy in PI-RADS 5 lesions between 83 and 97% for low and intermediate-risk PCa and 62–81% for clinically significant PCa (Gleason 7a or greater) [3, 8, 9, 15]. Although the detection rate of PCa is high in PI-RADS 5 lesions, cases of benign findings have been described [10, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies describe rates for malignancy in PI-RADS 5 lesions between 83 and 97% for low and intermediate-risk PCa and 62–81% for clinically significant PCa (Gleason 7a or greater) [3, 8, 9, 15]. Although the detection rate of PCa is high in PI-RADS 5 lesions, cases of benign findings have been described [10, 16].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally known that inflammation within the prostate can mimic PCa in the mpMRI [7, 10, 16, 17]. As prostatitis can lead to early contrast enhancement, low ADC values appear as hypointense lesions in the mpMRI similar to cancer [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that only in 9% of the FP cases for the inexperienced radiologists and in 50% of the FP cases for the experienced radiologist technical issues could have been the reason for a FP lesion. A study by Sheriden et al [23] reported that 28% of the FP PIRADS 5 lesions could have been missed at biopsy. The difference with our study is that they only investigated PIRADS 5 lesions that are usually large and therefore technique-wise less likely to be missed at biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we were not able to analyze false negatives and their relation to reader experience, which could have been done if the reference standard would have been prostatectomy specimens or if longterm follow-up data would have been available. Third, this study did not investigate other factors potentially associated with a FP reading, such as clinical variables and apex-base location [23]. Fourth, this study consisted of patients who had received prior biopsy (either negative or with cancer but on active surveillance) possibly reducing the future generalizability of the results.…”
Section: Discussionmentioning
confidence: 99%
“…5). False positive results may be due to misinterpretations of nodules of stromal benign prostatic hyperplasia within the central gland, due to large ISUP = 1 cancers or due to inflammation [22,23]. Non-cancer causes of positive MRI decrease with higher PI-RADS scores.…”
Section: When Mri Is Positivementioning
confidence: 99%